Dipeptidyl Peptidase-4 Regulation of SDF-1/CXCR4 Axis: Implications for Cardiovascular Disease - Zhong, Jixin; Rajagopalan, Sanjay (Frontiers in Immunology, 2015)
Dipeptidyl peptidase-4 (DPP4) is a ubiquitously expressed protease that regulates a diverse number of physiologic functions. As a dipeptidase it exerts its catalytic effects on proteins/peptides with proline, alanine or serine in the penultimate (P1) amino acid residue from the amino terminus. The evidence to date supports an important effect of DPP4 in catalytic cleavage of incretin peptides and this perhaps represents the main mechanism by which DPP4 inhibition improves glycemic control. DPP4 also plays an important role in the degradation of multiple chemokines of which such as stromal-cell-derived factor-1 (SDF-1, also known as CXCL12) is perhaps an increasingly recognized target, given its importance in processes such as hematopoiesis, angiogenesis and stem cell homing. In the current review, we will summarize the importance of DPP4-mediated enzymatic processing of cytokines/chemokines with an emphasis on SDF-1 and resultant implications for cardiovascular physiology and disease.